1968
DOI: 10.1530/jrf.0.0160463
|View full text |Cite
|
Sign up to set email alerts
|

The Post-Natal Development of the Reproductive Tract of the Suffolk Ram, and Changes in the Gonadotrophin Content of the Pituitary

Abstract: The growth of the pituitary and of the reproductive tract of Suffolk rams from birth to 168 days of age has been studied. Pituitary icsh and fsh concentrations were determined by bio-assay. The pattern of testicular androgen production has been examined using chemical and histological techniques and the relationship to spermatogenesis studied. Pituitary gonadotrophin content increased sharply from 42 days of age but was only weakly correlated with other parameters measured.The androstenedione : testosterone ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
31
1
2

Year Published

1974
1974
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 15 publications
14
31
1
2
Order By: Relevance
“…Normal spermatogenesis was evident in all rams aged 180 days or older. The histological data of the present study are in close agreement with the findings of Carmon and Green (1952), Courot (1962) and Skinner et al (1968). Testicular Carnitine Acetyltransferase.…”
Section: Resultssupporting
confidence: 92%
“…Normal spermatogenesis was evident in all rams aged 180 days or older. The histological data of the present study are in close agreement with the findings of Carmon and Green (1952), Courot (1962) and Skinner et al (1968). Testicular Carnitine Acetyltransferase.…”
Section: Resultssupporting
confidence: 92%
“…The central collecting sinus of each lobule had similar pseudostratified epithelium into which open the glandular tubes (Dellmann & Eurell). Three type of cells were identified in the pseudostratified epithelium containing A, B and C. It was also described earlier in goat (Yao & Eaton;Wrobel, 1970;Gupta & Singh, 1982;Plöen, 1980;) sheep (Skinner et al, 1968;Singh et al, 1980) and buffalo (Sudhakar et al). Table I.…”
Section: Resultssupporting
confidence: 65%
“…This finding goes hand in hand with Fahmy and Osman [10], Abdel-Raouf [16], Ghonimi et al [33], Amselgruber and Feder [36] in bull, Aumüller and Seitz [37] in bovines, Abbas [15], Skinner et al [38] in ram, Wrobel [39] in goat, Brewster [27] in human and Veneziale et al [40] in guinea pigs who reported that the secretory end pieces of seminal glands were found lined by two types of cells; columnar cells with variable height and low basal cells. While, the three types of cells; A, B and C have been identified by Yao and Eaton [21], Gupta [30], Gupta and Singh [41] in goat, Ploen [42], Singh et al [43] in ram and Chandrapal [11], Sudhakar et al [23] in buffalo and also Aumüller and Seitz [37] in bovines.…”
Section: Discussionmentioning
confidence: 78%